How stimulating creativity via E-Portfolios affects student learning and assessment - Zanou, Eleni (Language Center, Cyprus University of Technology, 2020)
The main purpose of this study is to investigate how e-Portfolios affect student language learning and assessment and whether the e-Portfolios can influence student performances on selected 21st Century skills, mainly on creativity, but including critical thinking, communication, collaboration, technological literacy, initiative and self-direction. The methodology is based on action research design where a specific intervention is designed to improve teaching practices and empower students through research involvement in Cyprus public school setting. This dissertation suggests an alternative method of student assessment/learning and development of creativity involving digital tools. The data collection follows a mixed method approach and includes the use of Torrance Tests of Creative Thinking (TTCT), semi and fully structured questionnaires, interviews and student reflections. The findings indicate that the e-Portfolio implementation facilitates students’ engagement in deep understanding of the material creating a positive attitude toward assessment. Likewise, e-Portfolios allow students to apply their knowledge via technology as well as to develop skills such as critical thinking, collaboration, communication, technological literacy, initiative and self-direction, and creativity. Moreover, all aspects of creativity (some more than others) appear to be enhanced, because of the variety of mechanisms activated by the process of the e-Portfolio implementation.
Keywords: e-Portfolios; Creativity; 21st century skills; 21st century skills